E2-SR: a novel energy-efficient secure routing scheme to protect MANET-IoT - Ponguwala, Maitreyi; Rao, Sreenivasa (IET communications, 2019)
Integration of mobile ad hoc networks (MANETs) and internet of things (IoT) becomes an emerging paradigm to enable opportunistic communication in IoT. However, the lack of infrastructure in MANET increases involvement of adversaries in IoT environment. Thus security provisioning against severe adversaries is still challenging in MANET-IoT. In this paper, we propose an energy efficient secure routing (E2-SR) scheme to ensure data security and integrity in MANET-IoT. We adapt Certificate based authentication in Hash Chain based Certificate Authentication (HCCA) scheme. Cluster formation is involved with secure verification of IoT devices by elliptic curve group law formulations. For cluster formation, secure dual head clustering with elliptic curve verification (SDHC-EC) algorithm is proposed. Secure routing is enabled by a new Worst Case Particle Swarm Optimization (WC-PSO) algorithm. The WC-PSO algorithm is supported by dual state markov chain model (DS-MCM) for security enhancement. Data security is ensured with data integrity using novel dual XOR-Rivest Cipher6 Encryption with Fuzzy Evaluation (DXOR-RC6 with FE) algorithm. The proposed MANET-IoT network is modeled and tested in ns-3.26 environment. The evaluation shows that E2-SR achieves better results in packet delivery ratio, throughput, residual energy, and routing overhead.